Automatic Fire Pump System Menggunakan Smart Relay Zelio dan Monitoring Tekanan Air Raspberry Pi di PT. Eastern Pearl Flour Mills - Rammadhan, Wahyu; Rofiq Azis, Muhammad; Lewi, Lewi; Hamzah, Firman (Politeknik Negeri Ujung Pandang, 2025)
Abstract: Occupational Health and Safety (OHS) is a crucial aspect in industry, especially in preventing and addressing fire hazards that can cause major material damage and even loss of life. PT. Eastern Pearl Flour Mills currently has a fire pump system, but its operation is still done manually and is not yet equipped with real time monitoring, reducing operational efficiency and response to emergency conditions. This research aims to design an Automatic Fire Pump System capable of activating three types of fire pumps Jockey Pump, Electric Pump, and Diesel Pump automatically using a Smart Relay Zelio. In addition, the system is equipped with a real time pressure monitoring feature using Raspberry Pi Pico W connected to a Firebase platform, and displayed in a web interface. The system operates based ON inputs from pressure switches and 4–20 mA pressure sensors, which are converted into digital data via Raspberry Pi. In automatic mode, the Smart relay controls the pumps according to the pressure levels detected. In manual mode, the user can activate the pumps remotely through the Firebase-based web interface. The test results show that the system can operate properly in both modes, with accurate and stable pressure readings, as well as responsive pump control. The system significantly improves the speed of detecting low pressure, reduces the risk of manual failure, and enhances overall safety and operational efficiency of the fire protection system at PT. Eastern Pearl Flour Mills.